Ursodeoxycholate inhibits mast cell activation and reverses biliary injury and fibrosis in Mdr2−/− mice and human primary sclerosing cholangitis. (November 2018) - Meng, Fanyin; Kennedy, Lindsey; Hargrove, Laura; Demieville, Jennifer; Jones, Hannah; Madeka, Taronish; Karstens, Allen; Chappell, Kevin; Alpini, Gianfranco; Sybenga, Amelia; Invernizzi, Pietro; Bernuzzi, Francesca; et al.
Abstract Ursodeoxycholic acid (UDCA) is used to treat biliary disorders; and, bile acids alter mast cell (MC) histamine release. MCs infiltrate Mdr2−/− mice liver (model of primary sclerosing cholangitis (PSC)). MC-derived histamine increases inflammation, hepatic stellate cell (HSC) activation and fibrosis. The objective was to determine the effects of UDCA treatment on MC infiltration, biliary damage, inflammation and fibrosis in Mdr2−/− mice and human PSC. Wild-type and Mdr2−/− mice were fed bile acid control diet or UDCA (0.5% wt/wt). Human samples were collected from control and PSC patients treated with placebo or UDCA (15 mg/kg/BW). MC infiltration was measured by immunhistochemistry and quantitative polymerase chain reaction (qPCR) for c-Kit, chymase, and tryptase. The HDC/histamine/histamine receptor (HR)-axis was evaluated by EIA and qPCR. Intrahepatic bile duct mass (IBDM) and biliary proliferation was evaluated by CK-19 and Ki-67 staining. Fibrosis was detected by immunostaining and qPCR for fibrotic markers. Inflammatory components were measured by qPCR. HSC activation was measured by SYP-9 staining. Inflammation was detected by qPCR for CD68. In vitro, MCs were treated with UDCA (40 μM) prior to HA secretion evaluation and coculturing with cholangiocytes or HSCs. BrDU incorporation and fibrosis by qPCR was performed. UDCA reduced MC number, the HDC/histamine/HR-axis, IBDM, HSC activation, inflammation, and fibrosis in Mdr2−/− mice and PSC patients. In vitro, UDCA decreases MC-histamine release, which was restored by blocking ASBT and FXRβ. Proliferation and fibrosis decreased after treatment with UDCA-treated MCs. We conclude that UDCA acts on MCs reducing histamine levels and decreases the inflammatory/hyperplastic/fibrotic reaction seen in PSC. Ursodeoxycholic acid (UDCA) is used to treat biliary disorders; and, bile acids alter mast cell (MC) histamine release. Following liver injury like primary sclerosing cholangitis in mice and humans, MCs infiltrate. MC-derived histamine increases biliary damage, fibrosis, and inflammation. UDCA treatment decreases these parameters via reduced MC activation. The bile acid rsodeoxycholic acid (UDCA) is the choice of treatment for primary biliary cholangitis patients with abnormal liver enzymes; however, its mechanism is not clear, and is the focus of this investigation. Bile acids alter mast cell (MC) histamine release. Following liver injury, such as that seen in primary sclerosing cholangitis, MCs infiltrate the liver. MC-derived histamine increases biliary damage, fibrosis, and inflammation. UDCA treatment decreases these parameters via reduced MC activation.